PELATIHAN KETERAMPILAN KOMUNIKASI BAHASA INGGRIS PARA GURU SMA NEGERI 1 NAMOHALU ESIWA BERBASIS KOMUNITAS - Zalukhu, Atalisi; Cahyani, Aliya Noor; Zendrato, Feronika (Merwinspy Publisher, 2025)
This community service program was implemented at SMA Negeri 1 Namohalu Esiwa to improve the English communication skills of high school teachers. Many teachers in the area face challenges in using English effectively during classroom interactions, which impacts the teaching process and student learning outcomes. To address this issue, a community-based training program was designed and implemented, consisting of workshops, peer-teaching sessions, role-playing activities, and microteaching practices. The training emphasized practical communication strategies that teachers could immediately apply in their classrooms. Evaluation was conducted through pre- and post-test assessments, reflective reflections, and feedback questionnaires. The results showed a significant increase in teachers' confidence and ability to use English communicatively in teaching contexts. This program demonstrates that community-based training can serve as an effective model for continuing professional development, particularly for teachers in rural areas.